TOKOH-TOKOH TASAWUF YANG BERPENGARUH DALAM PEMIKIRAN DAN PERKEMBANGAN PERADAPAN ISLAM ZAMAN MODREN - Johardi, Johardi; Saputra, Riki; Saifullah, Saifullah (Ensiklopedia of Journal, 2025)
Sufism is an important dimension of Islam that focuses on developing spirituality through cleansing the soul and closeness to Allah. This article aims to explore the contribution of Sufism figures such as Ibn Ata'illah al-Sakandari, Al-Muhasibi, and Abdul Qadir al-Jailani to modern Islamic thought. This study takes a qualitative approach and a literature study method to look at the main works of Sufi figures as well as other literature that supports them. The goal is to find out how their teachings can help us deal with the spiritual and social problems of today. The research results show that concepts such as makrifah, muhasabah, and asceticism not only remain relevant but also provide practical guidance for individuals and society in facing materialism, alienation, and moral crises in modern times. Modern Sufism teachings are able to offer a balance between spiritual and material needs, create social harmony, and encourage holistic character development. It is hoped that this article will provide new insight into the importance of Sufism in building a meaningful life amidst contemporary challenges.Keywords: Sufism, Ibn Ata'illah, Al-Muhasibi, Abdul Qadir al-Jailani, modern life